PRIORITY SCENARIOS OF THE MANAGER'S BEHAVIOUR IN THE ORGANIZATIONAL CONFLICT ON THE EXAMPLE OF THE JSC «RAMENSKOYE INSTRUMENT-MAKING PLANT» - O. Fomicheva (Вестник университета)
The organizational conflict from the position of participation of the manager has considered. He is particularly more responsible for the optimal use of resources: their improvement and multiplication. The article makes an analysis of 3 positions, in which the manager can take part: participant, mediator and as an «example of behaviouor». The necessity of developing a training program for managers has justified. Recommendations for the manager, for each of the 3 roles have offered. A General action plan has formulated for both the personnel management service and the management. As an example, the organization of Joint-stock company «Ramensky instrument-making plant» has chosen.